Student perception of sustainability in industry: a case study in an undergraduate petroleum processing course - Chakraborty, Sourojeet; Kalhori, Sadafnaz Kashi; Gonzalez, Yris; Mendoza, Jorge; Galatro, Daniela (Frontiers in Education, 2024)
Research demonstrates a predominantly negative public perception of the oil and gas (O&G) industry, regardless of initiatives created to minimize the environmental impact. This might be attributed to a lack of open communication and debate spaces where these initiatives are learned and discussed. To test our hypotheses within a university setting, a major revamp of the course “Petroleum Processing” in our university was implemented, where sustainability concepts and open discussion were assimilated into the lecture content. Pre- and post-surveys were conducted to assess students’ perceptions regarding sustainability in the O&G industry before and after the course. Perceptions remained unchanged following course delivery. However, students believe they are more informed about the sustainability approaches implemented.